Termite Problems in Arid Zones and their Management - Thakur, R. K. (Indian Forester, 1996)
Tennites cause heavy loss to agricultural crops, pastures, forest nurseries and young plantations, and are thus considered as great threat to the developmental programmes in the arid zones. Observations were made on the tennite problems in arid areas ofGujarat, Punjab, Haryana and some parts of Rajasthan during 1979-85 and 1988-89. Anacanthotermes macrocephalus, Coptotermes heimi. Odontotermes obesus and Microtermes obesi were recorded as serious pests of agriculture, forestry and horticulture, and Heterotermes indicola causes extensive damage to wood work in buildings. Pest status of these tennites in arid zones is discussed.